Xanthan gum biopolymer-based soil treatment as a construction material to mitigate internal erosion of earthen embankment: A field-scale - Kwon, Yeong Man; Moon, Jun Ho; Cho, Gye Chun; Kim, Young Uk; Chang, Ilhan (Construction and Building Materials, 2023)
Biopolymers, which are naturally produced polymers, exhibit hydraulic and mechanical properties, and have low environmental impact. Therefore, they can be employed as an alternative to conventional civil engineering materials for internal erosion prevention. However, the internal erosion behavior of biopolymer-treated soils in a full-scale embankment is yet to be thoroughly investigated. This study focused on the potential of using xanthan gum biopolymer for internal erosion control in earthen embankments. To this end, both laboratory and full-scale investigations were conducted for analyzing its influence on the prevention of internal erosion. The laboratory tests showed that a 1% xanthan gum treatment demonstrated optimal characteristics for embankment building with enhanced soils’ plasticity and mechanical strength. Full-scale embankments were constructed using both untreated and 1% xanthan gum treated earthen materials with simulated internal erosion beneath the box culvert to test the effect of xanthan gum on mitigating internal erosion. The results revealed that xanthan gum successfully minimized the expansion of internal erosion through particle bonding, enhanced apparent cohesion, and pore-clogging. The untreated embankment eroded rapidly via seepage flow and collapsed within 1,500 s, while the 1%-XG-treated embankment retained its structure without considerable erosion until 2,500 s. Thus, xanthan gum is an environmentally friendly construction material that can achieve sufficient embankment stability with a small weight ratio (1% of total soil).
Keywords: Biopolymer-based soil treatment; Earthen embankment; Earthen levees; Engineering materials; Field application; Field scale; Internal erosion; Large scale testing; Optical fiber sensor); Soil treatments; Biopolymer; Biopolymer-based soil treatment (BPST); Earthen embankment; Earthen levee; Field application; Internal erosion; Large-scale testing; Optical fiber sensor); Xanthan gum